Case with a Nonreassuring Fetal Status Induced by Massive Hematemesis due to Mallory-Weiss Tear That Required Emergency Cesarean Section at 38 Weeks' Gestation - Takashi Suzuki; Maiko Wagata; Hiroko Konno; Takahiro Ito; Yuichi Torii; Takeshi Murakoshi (Hindawi Limited, 2015)
We describe a rare case of Mallory-Weiss tear with massive hematemesis at 38 weeks' gestation. A 35-year-old woman presented with epigastralgia followed by massive hematemesis. An emergency endoscopy indicated active pulsatile bleeding at the esophagocardial junction. Although an emergency endoscopic hemostasis was successful, late decelerations without acceleration on cardiotocogram were observed. Therefore, the patient underwent emergency cesarean section, along with blood transfusion, following the endoscopic hemostasis. The hemoglobin level just before the operation was 5.1 g/dL. We suspected that massive hematemesis induced maternal acute anemia and hypovolemia, which resulted in a nonreassuring fetal status. Hence, urgent endoscopic hemostasis, adequate blood transfusion, and emergency cesarean section were needed. Mallory-Weiss tear during the third trimester may have a possibility of massive hematemesis and urgent blood transfusion, emergency endoscopic hemostasis, and emergency cesarean section may be needed.